Editorial English - Abar, Celina A. A. Pereira (Revista do Instituto GeoGebra Internacional de São Paulo, 2022)
This second issue of volume 11 of the 2022 journal presents seven articles and an experience report that seek to cover the different possibilities and paths with which GeoGebra can be investigated and, in a new space "Proposals for Action", we have two proposals that meet the respective objectives. For the next issues of the journal, other proposals will be welcomed to this section.